Pragmatic Function of Gitaigo in Genshin Impact Dialogues: A Contextual Analysis of Japanese Onomatopoeia - Zhendyvavellany Putrilizka; Parastuti; Ina Ika Pratita; Urip Zaenal Fanani (Universitas Negeri Padang, 2026)
This study discusses the use of gitaigo onomatopoeia in the game Genshin Impact through a pragmatic approach. Gitaigo is a type of Japanese onomatopoeia used to describe conditions, states, and feelings without producing actual sounds. The use of gitaigo in utterances plays an important role in clarifying meaning and communicative functions within a particular context. This study aims to describe the context of gitaigo usage and analyze its pragmatic functions in utterances found in the game Genshin Impact. This research employed a descriptive qualitative method with a pragmatic approach. The data sources consisted of dialogues and narrations in the game containing gitaigo expressions. The data were collected using observation and note-taking techniques and then analyzed based on their contextual usage. The results show that gitaigo in Genshin Impact is used to describe physical conditions, sensory experiences, atmospheres, and certain situations in a more expressive manner. Furthermore, the pragmatic functions of gitaigo are used to clarify the speaker’s intention, emphasize particular conditions, and strengthen meaning in communication. Therefore, gitaigo plays an important role in supporting communicative effectiveness in Japanese utterances within digital media.